(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
Fish produces many types of behavior as response to stress that cause by pollution. Respiration and locomotion are two main responses that normally produced. As such, study on these responses is important especially for pollution monitoring. Study on fish respiratory and locomotive behaviors was undertaken using multispecies freshwater bio indicator (MFB). Signal produced by fish determines the specific frequency range for respiratory and locomotive activities. This study aims to produce unstressed and stress signals (ventilation and locomotion) as a respond to TSS contamination. Three common species namely guppy (Poecilia reticulata), fighthing fish (Trichopsis vitatus) and Malaysian masher (Tor tambroides) were used and test was conducted for 24-hour period. Result of the study indicates that ventilation and locomotion activities were clearly separated by different wavelength for all species but each species produced similar wavelength for each activity. A paired t-test confirmed that wavelength for each activity from all species was not differ significantly (p > 0.05, Î± = 0.05). Only ventilation produce significant respond to TSS load and ventilation percentage signal was increase as TSS concentration increase. Similar respond was observed for all species. This study demonstrates that TSS contamination can be detected at early stage and maximum TSS load into the river system could be estimated.